Emotional labour and burnout syndrome among nigerian politicians - O Odor, Hillary; Josephine; C Ugbechiec, Kingsley (Journal of Management and Science, 2020)
The manner in which politicians express their emotions while interacting with the electorates determines how the electorates will perceive the ability of the politicians to fulfill their electoral promises if voted into power. This paper aims to investigate the relationship between politicians’ emotional labour and burnout syndrome. The sample consists of 400 politicians spread around Four (4) Local Government Areas in Delta State, namely: Aniocha North, Aniocha South, Oshimili North, and Oshimili South Local Government Area of Delta State, Nigeria, irrespective of their political party affiliations. Emotional Labour Scale developed by Diefendorff, Croyle, and Gosserand (2005), and the Maslach Burnout Inventory developed by Maslach and Jackson (1986) were used to collect data from the respondents. Data analysis was done using descriptive statistics, t-tests, Analysis of Variance (ANOVA) and regression analysis. Results indicate that the politicians exhibit a high level of surface acting in the discharge of their responsibilities. It also revealed that they show the least amount of genuine emotions in their work, while the level of deep acting is moderate.In terms of burnout, politicians experience a very high level of emotional exhaustion, a moderate level of both depersonalization and lack of personal accomplishment. Results of the regression analysis show that the three dimensions of emotional labour (surface acting,deep acting and genuine emotions) are very important predictors of burnout among politicians. Consequently, this present results offer a very crucial and innovative contribution to emotional labour literature and more studies are therefore required in order to expand the scope of this research to ensure a more adequategeneralization.